Collagen Extracted from Bigeye Tuna (Thunnus obesus) Skin by Isoelectric Precipitation: Physicochemical Properties, Proliferation, and Migration Activities - Xinhui Lin; Yinyue Chen; Huoxi Jin; Qiaoling Zhao; Chenjuan Liu; Renwei Li; Fangmiao Yu; Yan Chen; Fangfang Huang; Zuisu Yang; Guofang Ding; Yunping Tang (Marine Drugs, 2019)
Collagen was extracted from bigeye tuna (Thunnus obesus) skins by salting-out (PSC-SO) and isoelectric precipitation (PSC-IP) methods. The yield of the PSC-IP product was approximately 17.17% (dry weight), which was greater than the yield obtained from PSC-SO (14.14% dry weight). Sodium dodecyl sulfate-polyacrylamide gel electrophoresis analysis indicated that collagen from bigeye tuna skin belongs to collagen type I. Inductively coupled plasma mass spectrometry results indicate that the heavy metal abundance in PSC-IP was lower than the maximum acceptable amounts according to Chinese regulatory standards. In addition, results from a methylthiazolyldiphenyl-tetrazolium bromide assay and an in vitro scratch assay demonstrated that PSC-IP could promote the proliferation and migration of NIH-3T3 fibroblasts. Overall, results suggest PSC-IP could be used to rapidly extract collagen from marine by-products instead of traditional salting-out methods. Collagen from bigeye tuna skin may also have strong potential for cosmetic and biomedical applications.